Reviews - Ray McAleese; Philip Barker; David C. Arnott; J. Douglass Klein (Association for Learning Technology, 1999)
There is something curious about a book title that associates the terms 'university' with 'learning' - at least in the way Bowden and Marton have chosen. While most would agree that universities serve society through 'teaching, research and community service', it is the simple description of a new breed of institution that is about learning - not teaching or research or community service, that is disconcerting. The authors have a principled reason for so doing. After all - what is the outcome of teaching - but learning? What is the outcome of research if not better informed debate and 'learned' scientists? What is the outcome of community service if not people better able to make sense of the world in which they live? But a University of Learning . . . that is a different matter - or so it has been up to now. Universities must address the needs of learners. Learning as we now tend to see it - is about '. . . the process whereby knowledge is created through the transformation of experience' (Kolb, 1984). The needs of learners require teachers to construct challenging opportunities. Opportunities for learners to puzzle and reflect. Through experimentation and conceptualization, learners transform events, ideas, experiences into testable hypotheses - setting their reflections against personal frameworks.